2022
DOI: 10.1364/oe.449016
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transmissive remote phosphor configuration for a laser-driven high-luminance white light source

Abstract: To realize laser-driven high-luminance white light sources, many reflective configurations have been studied, often resulting in a challenging optical design. In this paper it is demonstrated that the efficacy of a transmissive configuration can be significantly enhanced by using a sapphire half-ball lens as out-coupling optic. This lens not only improves efficiency, but also drastically increases the potential light output due to improved heat dissipation from the single-crystal phosphor converter. Both claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…[14][15][16] Due to the high laser power density and a small radiation spot of the blue laser diode, the fluorescent layer is subject to high laser radiation energy and fluorescent conversion heat, resulting in high temperature in the spot position of the fluorescent layer. [17][18][19][20] The traditional fluorescent layer is a mixture of a phosphor and an organic resin. Due to the poor heat resistance and low thermal conductivity of organic resin, the problem of resin carbonization and thermal quenching of the phosphor occurs at high temperatures, which makes the organic fluorescent layer meet the packaging requirements of white light laser diodes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Due to the high laser power density and a small radiation spot of the blue laser diode, the fluorescent layer is subject to high laser radiation energy and fluorescent conversion heat, resulting in high temperature in the spot position of the fluorescent layer. [17][18][19][20] The traditional fluorescent layer is a mixture of a phosphor and an organic resin. Due to the poor heat resistance and low thermal conductivity of organic resin, the problem of resin carbonization and thermal quenching of the phosphor occurs at high temperatures, which makes the organic fluorescent layer meet the packaging requirements of white light laser diodes.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphor/silicone composite is widely used as a color converter in LEDs, however, it is limited used in pc-WLD as its low thermal stability. The optical density of an LD is extremely high reach up to 6.9 W/mm 2 [10]. Excessive optical density will cause the thermal quenching and carbonization of phosphor/silicone composites [11].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance forward light extraction efficiency, Rondelez et al proposed a novel optical scheme in which the SCP was fixed on a sapphire half-ball lens [10], which resulted in a 150% improvement in luminous flux. Wagner et al [25] revealed that the photoluminescence intensity of transmissive white laser light source improves with the increase in the roughness of the surface of the phosphor.…”
Section: Introductionmentioning
confidence: 99%